2017
DOI: 10.1002/slct.201701514
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Active Center of Cu‐Based Catalyst for Low Temperature Methanol Synthesis from Syngas in Liquid Phase: The Contribution of Cu+ and Cu0

Abstract: LaCuMn catalyst was prepared under different reduction temperature and passivation time, and used to catalyze CO hydrogenation to methanol in liquid phase. The effect of reductive copper species on the catalytic activity and the product distribution was studied. The results showed that the surface content of reductive copper species greatly affect the catalytic activity and the approximate molar ratio of Cu+ to Cu0 was important. The mixture of CuZn/AC‐N2 with only Cu+ and CuZn/AC‐H2 with only Cu0 was utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Shi, Tsubaki, and coworkers 484 used SiO 2 to support Cu and ZnO and obtained a smaller Cu crystal size and a higher Cu dispersion, which led up to 55% methanol yield (Table 14, entry 28). Besides Cu/ZnO, a LaCuMn catalyst was developed by the Chen group 493 and presented 69.1% yield of methanol at 170 °C (Table 14, entry 37).…”
Section: Catalyst Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi, Tsubaki, and coworkers 484 used SiO 2 to support Cu and ZnO and obtained a smaller Cu crystal size and a higher Cu dispersion, which led up to 55% methanol yield (Table 14, entry 28). Besides Cu/ZnO, a LaCuMn catalyst was developed by the Chen group 493 and presented 69.1% yield of methanol at 170 °C (Table 14, entry 37).…”
Section: Catalyst Developmentmentioning
confidence: 99%
“…They selected K 2 CO 3 as the additive and HCOOK was confirmed to be the intermediate for the formation of methyl formate when using methanol as solvent. K 2 CO 3 was also used by other researchers ,, to enhance the methanol yield in this process. In 2008, the Fujimoto group employed alkali formate as the additive and observed that the space time yield of methanol over a Cu/MgO-Na catalyst with these additives followed the order: HCOONa > HCOOK > HCOORb > HCOOCs > HCOOLi.…”
Section: Applications Beyond Traditional Synthesis and Productionsmentioning
confidence: 99%
“…This sample differed from the other starch containing specimens by particle size and Cu phases present. Previous results have shown that in the presence of 20 bar CO/2H 2 at 100 °C, reduction of Cu 2+ is rapid [ 10 , 28 ], and that the active Cu phase for the MeOH synthesis is assumed to be in the Cu + /Cu° oxidation state [ 29 ]. This implies that it is not likely that the Cu phase in the B 1 NS catalyst contributed to the difference in the activity but rather the absence of starch.…”
Section: Resultsmentioning
confidence: 99%